Investigation Of Mechanical & Wear Characteristics Of T6 Heat Treated Thixoformed Aluminium Alloy Composite - Salleh, Mohd Shukor; Yahaya, Saifudin Hafiz; Abdul Rahman, Azrul Azwan; Othman, Intan Sharhida; Al Zubaidi, S.S.; Zulkifli, K. (Penerbit UTeM, 2020)
Thixoforming of aluminium alloy has been making a strong presence in the near net shape part production for the automotive and aerospace industries due to its process superior properties output in comparison to the other conventional methods. Improvement of the properties would surely further add to the already advantageous process above others.This study investigates the mechanical and wear behaviours of thixoformed Al-Si-Cu alloy when multi-walled carbon nano tubes (MWCNT) infusing into the thixoforming process. A new approach established using the mechanical stirring casting techniques produces a well-bind composite mixture of non-dendritic aluminium mixed with different content (0.5, and 0.75) of MWCNTs. The approach enclosed the MWCNTs with 0.5wt.% of Magnesium (Mg) powder as a wetting agentinto an aluminium wrapping and stirred it with LM4 for 10 and 15 min interval inside a furnace. The feedstock produced would be thixoformed before finally being applying T5 and T6 heat treatment. The microstructure of eacH specimens is characterised while the mechanical (tensile and hardness) and wear properties aremeasured according to each requirement. The outcome shows formation of non-dendritic microstructure with homogeneous distribution phase of the MWCNTs within it. The DOE analysis of the highest MWCNT content and stirring time after a T6 heat treatment reveals the highest hardness and UTS result of 94.6 HV and 246.2 MPa respectively. The Taguchi analysis also reveals that heat treatment was the most significant factor contributing towards the improvement. The heat-treated samples increase the hardness and tensile strength approximately 30% compared to an as-cast and give around 20% increment of wear resistance to the specimen